2010
DOI: 10.1177/0165025409351657
|View full text |Cite
|
Sign up to set email alerts
|

Associations among child care, family, and behavior outcomes in a nation-wide sample of preschool-aged children

Abstract: Canadian data based on maternal reports for a nationally representative sample of 4,521 4-5-year-olds were used to examine associations among child care, family factors, and behaviors in preschool-aged children. Linear regressions testing for direct and moderated associations indicated that regulated home-based care was associated with less physical aggression and less prosocial behavior while high process quality in home-based care was associated with greater prosocial behavior. Among children in home-based s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 72 publications
(86 reference statements)
2
39
1
5
Order By: Relevance
“…Other researchers, however, have been unable to confirm the positive correlation between child care quantity and child behavior problems (McCartney et al, 2010;Romano, Kohen & Findlay, 2010). It may be that the link between time spent in child care and behavioral outcomes is influenced by other aspects of child care (e.g., quality) as well as by individual and family characteristics.…”
Section: Child Care Characteristicsmentioning
confidence: 96%
See 1 more Smart Citation
“…Other researchers, however, have been unable to confirm the positive correlation between child care quantity and child behavior problems (McCartney et al, 2010;Romano, Kohen & Findlay, 2010). It may be that the link between time spent in child care and behavioral outcomes is influenced by other aspects of child care (e.g., quality) as well as by individual and family characteristics.…”
Section: Child Care Characteristicsmentioning
confidence: 96%
“…Types of non-parental care arrangements typically include care in the child's home by a relative or non-relative, care in another individual's home by a relative or non-relative, and center-based care. In Canada, child care centers are licensed by a government body, and therefore all standards regulating adult-to-child ratios, group size, caregiver education, and the health and safety standards of the physical space typically are met (Romano et al, 2010). In comparison, regulation for home-based care may occur through a family daycare agency or a provincial/state ministry responsible for child care; however, this occurs on a voluntary basis and provincial/state licensing requirements often vary tremendously (National Association of Child Care Resource & Referral Agencies, 2008;Romano et al, 2010).…”
Section: Child Care Characteristicsmentioning
confidence: 99%
“…Moderate associations were seen between higher risk of having a child with a behavioral problem and the caregiver being less comfortable in parenting, appraising the child"s behavior as poor, higher levels of daily perceived stress, higher depression symptomatology, higher distortion in ratings, and higher parenting stress. Romano, Kohen, & Findlay (2010) used a nationally representative sample of 4,521 Canadian families of 4-5-year-olds. They found that low household income was linked with greater hyperactivity-inattention among children in poor quality home daycare facilities but not high-quality daycare facilities.…”
Section: Level Of Risk Of Having a Child With A Behavioral Problemmentioning
confidence: 99%
“…L'argumentaire développé précédemment rejoint le point de vue de Zachrisson, Dearing, Lekhal et Toppelberg (2013) qui concluent que le contexte sociopolitique, incluant les politiques de financement et l'accès aux services de garde spécifiques à chacun des pays, pourrait être à l'origine de l'incohérence des résultats qui portent sur la relation entre le nombre d'heures passées en milieu de garde et la manifestation de problèmes externalisés chez les enfants. Par exemple, des études canadiennes (Romano, Kohen et Findlay, 2010) et norvégiennes (Zachrisson et al, 2013) ne relèvent aucun impact négatif du temps passé en milieu de garde sur le comportement des enfants, alors que l'étude américaine du National institute of child health and human development early child care research network en arrive à des conclusions totalement différentes. À ce propos, on relève que les services de garde aux États-Unis s'adressent souvent à des familles de milieux défavorisés (exemple : le programme Head Start), alors que certains pays européens offrent des services à toutes les familles (Burger, 2010).…”
Section: Vers Une Perspective Intégrée Du Développement Humainunclassified